2009
DOI: 10.1007/s00394-009-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplementation on immunoglobulins, isoagglutinins and antibody response in children of low socio-economic status

Abstract: Supplementation of standard fermented milk with additional probiotics was not of benefit. The high natural rate of early microbial exposure in infants and children from a population of low socio-economic status living in a "less hygienic environment" may account for the absence of an additional immune-stimulating effect by supplementary probiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…We believe that the socioeconomic status and genetic background may explain the results. (9) Acomparison between two cities in São Paulo state showed high titers for both men and women with an increase in levels in recent years. (10) The authors did not stratify for age and the technique used for titration was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the socioeconomic status and genetic background may explain the results. (9) Acomparison between two cities in São Paulo state showed high titers for both men and women with an increase in levels in recent years. (10) The authors did not stratify for age and the technique used for titration was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that when there is an adequate immune response, the probiotics have no additive effect on the quantity of antibodies produced, but that their value lies in a boosting effect only for infants with a weak immunological response to vaccination. Prior studies have shown that infants in developing countries usually mount higher antibody titres following vaccination, than do infants from developed countries 23. This has been explained by the ‘hygiene hypothesis’ stating that early repeated antigenic stimulation by viral and bacterial infections stimulates a Th1 profile of the immune response, favouring IgG2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in public health and hygiene, and the steady decline in family size in the developed world can thus potentially favour a Th2 response, explaining the reduced ability to mount adequate antibody responses following exposure to infections or vaccination 9 14 24. Accordingly, Pérez et al 23 showed recently that probiotic supplementation has no effect on antibody responses following DTP-Hib and 23-valent pneumococcal vaccine in children of low socioeconomic status in Argentina. It is possible that probiotic supplementation is a safe way of ‘closing the gap’ between infants in developed countries and those from developing parts of the world, regarding early microbial colonisation and antigenic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…A yogurt of a lot provided for the volunteers was randomly tested six days after its expiration date, in which a bifidobacteria concentration of 1.74x10 6 CFU/g of yogurt was found. Coupled with the likely concentration of Lactobacillus, this would still be a probiotic food and bring benefits to people's health (19) , including celiac patients.…”
mentioning
confidence: 99%
“…The maintenance of pH values before and after probiotic ingestion may be related to time or quantity/concentration of the daily-consumed probiotic, being suggested that probiotic effects are dose-dependent (19) . However, the recommended dose by the literature was consumed in this study, which is between 10 6 e 10 11 CFU/day, depending on the desired effect (22) .…”
mentioning
confidence: 99%